PERSEPSI IBU HAMIL TENTANG PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI (P4K) DI KELURAHAN TANJUNG PINANG KOTA JAMBI TAHUN 2014 - Ruwayda Ruwayda (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
Based on data obtained from the Health Department in  2013 Puskesmas Tanjung Pinang is a health center that is not implemented and Program Planning and delivery Complication Prevention (P4K). It is known that high-risk pregnant women in PHC Tanjung Pinang and 284 pregnant women who had been referred to as many as 42 people with a variety of complications of hypertension, Haemoglobine <10 g%, a history of caesarean section and other complications. Planning labor is needed in the face of labor to prevent complications that would affect the safety of mothers and babies so that mothers do not experience delays and can get the appropriate services and timely.This research is a descriptive study with cross sectional approach undertaken in Tanjung Pinang of Jambi. The population in this study were pregnant women in antenatal check from January to June 2014 were residing in Tanjung Pinang as 158 people. Sampling techniques using simple random sampling with a sample of 60 people. This research was conducted in August 2014 using a questionnaire.The data in this study were analyzed by univariate.Results of the 60 respondents, that 50 (83.3%) of respondents have the knowledge of good, and 26 (43.3%) of respondents have the good perception of the Programme Planning and Delivery Complications Prevention (P4K). It is expected that the cooperation between the institutions involved in the implementation of Program Planning and Delivery Complications Prevention (P4K) for PHC Tanjung Pinang in order to carry back and Program Planning and delivery Complications prevention (P4K) for pregnant women working in the region as well as provide knowledge and counseling to pregnant women about the importance of preparation for childbirth, especially transportation and prospective blood donors.Keyword :  pregnant women, childbirth, prevention of complications